Pedagogical practices supported by mobile technologies: opportunities to enhance the learning of the student population - Villalobos-García, Melissa; Núñéz-Sosa, Olmer (Innovaciones Educativas, 2020)
In order to identify key aspects to enhance the use of mobile technologies in learning processes, a descriptive study is proposed comparing socioeconomic, educational and good use conditions of these resources in two populations of high school students: participants with at least two years of experience in using mobile technologies in class and participants who did not have such experience. From a comparative approach between the populations, it was identified that the students who receive pedagogical support to incorporate mobile technologies in their learning processes tend to consider themselves more competent users of said resources. They show a greater repertoire of knowledge about useful tools in the educational field, and show better conditions to safely use leisure spaces such as social networks. It is concluded that one of the greatest opportunities to enhance the use of mobile technologies in learning processes is related to the role that their teachers have in it, therefore favoring the development of technological appropriation in the teaching population is key within this type of educational proposals.